Part III – March 1968 - Papers - Polarization Effects in Insulating Films on Silicon-A Review - E. H. Snow; B. E. Deal (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Instability effects in semicanductor devices have long been attributed to the motion of charges on or within oxide layers on the surface. These effects are of critical importance in metal-insulator-semiconductor MIS) field-effect devices. For this reason, the capacitance-voltage or the conductance-voltage characteristic of these devices can be used as a sensitive detector to study charge transport and polarization effects in the oxide or insulator. A review is given of the results of such studies of thermally grown SiO2 as well as of other insulating films of importance in silicon technology. Three types of effects are distinguished. The first of these is the drift of mobile cations within the dielectric, examples being thermally grown SiO, which is often contaminated with sodium ions, and a variety of other glasses in which the mobile ions are a part of the glass composition. The second effect is a dipole-type polarization which occurs in phosphosilicate glass films obtained by reacting P2O5 with thermally grown SiO2. The third effect involves the transfer of charges between the dielectric and the silicon electrode. This occurs in silicon nitride and other deposited dielectrics. It is concluded that MIS studies have provided a powerful technique joy the study of charge transport and polarization effects in insulating films. The knowledge gained from these studies has led to an understanding of surface effects on conventional transistors and diodes as well as making possible stable MIS transistors. THE metal-insulator-semiconductor field-effect transistor is conceptually the oldest type of active semiconductor device.' The earliest attempts at making this device were frustrated because of high surface state densities at the interface between the semiconductor and the gate insulation.' However, by using a silicon substrate with thermally produced silicon dioxide as the gate insulation, this problem was solved and metal-silicon dioxide-silicon devices with good characteristics were made as early as 1960. 3 Yet it was still over 5 years before these devices became a commercial reality. This delay was largly due, not to surface states, but to stability problems associated with polarization effects within the insulating layer which caused the threshold voltage of the device to drift under temperature and bias treatments. The solution to these problems has not only made possible stable MIS devices, but it has added immensely to our understanding of failure mechanisms in conventional bipolar transistors and has added to the reliability of ali types of planar devices. In this review, we shall first describe the effects of various types of polarization phenomena on MIS device characteristics. Then, since thermally grown SiO, is by far the most important insulator used in these devices, we shall review historically the type of instabilities which have been observed in thermal oxides, the attempts at understanding and eliminating them, and the present status of the problem. We shall then turn our attention to the various deposited insulators which have been used, including lead glasses, phosphosilicate glass, vapor-deposited silicon oxide, and silicon nitride. Interestingly enough, many of these materials show polarization effects which are quite different from those generally observed in thermally grown SiO2. THE EFFECTS OF POLARIZATION PHENOMENA ON MIS CHARACTERISTICS The simplest MIS device and the one which has been most frequently used in the study of polarization effects is the MIS capacitor. Two modifications of this structure with single- and double-layer dielectrics are illustrated in Figs. l(a) and (b), respectively. The capacitance of this structure as a function of voltage applied to the metal gate electrode is plotted in Fig. 2 for the case of an n-type silicon substrate. When the silicon surface is accumulated (positive bias) the measured capacitance is just that of the insulating layer C. When the surface is inverted (negative bias), the capacitance is that of the insulator and a silicon depletion layer in series CoCs/(Co + Cs). Indicated on the horizontal axis of Fig. 2 is the voltage VT at which the silicon surface becomes strongly inverted. This voltage corresponds to the threshold or turn-on